2007
DOI: 10.1093/jee/100.2.495
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Uptake, and Transfer Efficiency of Fipronil in Western Subterranean Termite (Isoptera: Rhinotermitidae)

Abstract: The potential horizontal transfer ofnonrepellent termiticides has become an important paradigm to control termites in recent years. In this study, 14C-radiolabeled fipronil was used in a series of laboratory experiments to demonstrate the extent and ability of termites to transfer lethal amounts of fipronil to unexposed nestmates. Fipronil is an active and nonrepellent termiticide against western subterranean termites, Reticulitermes hesperus Banks, on sand at relevant doses. It exhibited delayed toxicity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 0 publications
9
88
0
Order By: Relevance
“…Bifenthrin was also found to have the highest activity against Reticulitermes hesperus when compared with other pyrethroids (Smith & Rust, 1990). Saran and Rust (2007) found that R. hesperus tunneled through untreated sand and stopped near the interface of fipronil treated sand. There was little tunneling in the treated sand, but termites tunneled close enough to obtain a lethal dose of fipronil.…”
Section: Soil Termiticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bifenthrin was also found to have the highest activity against Reticulitermes hesperus when compared with other pyrethroids (Smith & Rust, 1990). Saran and Rust (2007) found that R. hesperus tunneled through untreated sand and stopped near the interface of fipronil treated sand. There was little tunneling in the treated sand, but termites tunneled close enough to obtain a lethal dose of fipronil.…”
Section: Soil Termiticidesmentioning
confidence: 99%
“…Delayed toxicity can provide opportunity for horizontal transfer of the active ingredient, potentially reducing termite activity (Remmen & Su, 2005;Shelton & Grace, 2003). While there is some evidence of colony suppression or elimination following perimeter treatments with imidacloprid (Parman & Vargo, 2010), other studies have shown that a reduction in activity occurs over only a small portion of a colony's foraging range, making it unlikely that soil treatments affect the overall termite population (Osbrink et al, 2005;Rust & Saran, 2006;Saran & Rust, 2007;Su, 2005). This limited potential for transfer emphasizes the importance of bioavailability of termiticides in soil over an extended period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Saran and Rust [26] found that Reticulitermes flavipes tunneled through untreated sand and stopped near the interface of fipronil treated sand. There was little tunneling in the treated sand, but termites tunneled close enough to obtain a lethal dose of fipronil.…”
Section: /7mentioning
confidence: 99%
“…Non-repellent insecticides often maintain the property of nonrepellency even at high concentrations (up to 500 part per million in Reticulitermes flavipes Saran and Rust [26]. Fipronil is more toxic to insects than people and pets because it is more likely to bind to insect nerve endings through contact toxicity.…”
Section: /7mentioning
confidence: 99%
See 1 more Smart Citation